Study on Joothon: Metaphor of Poverty, Pollution and Humiliation: Exploring caste discrimination and its impact in Indian society (Journal of Advances and Scholarly Researches in Allied Education, 2021)
“Omprakash Valmiki, an accomplished Indian writer, has shown how the so-called higher caste in India oppresses and dominates the populace. The emphasis of this study is on how the upper caste controls the scheduled caste by many machinery such as custom, law, religion, culture, and language of the dominant group of individuals in power. In his work Joothan, the author includes a character from the category of minorities, labourers, and peasants. Omprakash, the protagonist, is forced to seed sugarcane on Fauz Sing's land despite the fact that his examination is coming. There are several evidences that support his muteness, which add to his sense of inferiority. Head teacher Kaliram's misbehaviour at school, working in Tyagi's home without pay, and keeping him out of extra-curricular activities at school are instances. He gets mistreated in all of these circumstances. The term also captures Valmiki's community's anguish, humiliation, and poverty, which they not only had to depend on but also cherished. Valmiki describes how to gather, preserve, and consume Joothan in great detail. His recollections of being assigned to guard and drying Joothan from crows to chicken, as well as the anguish and humiliation he felt when he realised the dried and reprocessed Joothan burned him again many years later. On one level, this is an autobiographical description of Valmiki's life, from his birth and upbringing as an untouchable in newly independent India in the 1950s through his pleasure in being a Dalit today. Joothan is also a record of the state of those who are now often referred to be erstwhile untouchable or exuntouchalble. The comment of Douglas Bom on Joothan encapsulates the topic of dominance in Indian culture